2021
DOI: 10.3390/w13192667
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Debris Flow Runout: A Case Study on the Mesilau Watershed, Kundasang, Sabah

Abstract: Debris flows are among the fatal geological hazards in Malaysia, with 23 incidents recorded in the last two decades. To date, very few studies have been carried out to understand the debris flow processes, causes, and runouts nationwide. This study simulated the debris flow at the Mesilau watershed of Kundasang Sabah caused by the prolonged rainfall after the 2015 Ranau earthquake. Several interrelated processing platforms, such as ArcGIS, HEC-HMS, and HyperKANAKO, were used to extract the parameters, model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The landslide deposits provided abundant sediments for subsequent remobilization as debris flows following heavy rainfall (highest rainfall intensity of 14.2 mm h −1 on 15 June 2015; Rosli et al, 2021a). Some detailed studies of debris flows were performed on limited areas through lidar techniques (Yusoff et al, 2016;Rosli et al, 2021a, b), but a comprehensive inventory of all the triggered landslides is still lacking and is the focus of this paper.…”
Section: The Study Area and The 2015 Sabah Earthquakementioning
confidence: 99%
See 1 more Smart Citation
“…The landslide deposits provided abundant sediments for subsequent remobilization as debris flows following heavy rainfall (highest rainfall intensity of 14.2 mm h −1 on 15 June 2015; Rosli et al, 2021a). Some detailed studies of debris flows were performed on limited areas through lidar techniques (Yusoff et al, 2016;Rosli et al, 2021a, b), but a comprehensive inventory of all the triggered landslides is still lacking and is the focus of this paper.…”
Section: The Study Area and The 2015 Sabah Earthquakementioning
confidence: 99%
“…The identification of the precise event that triggered the landslides can be challenging, and subsequent remobilizations may occur as well. In the Sabah case, slope movements were firstly triggered by the seismic shaking; later on, prolonged rainfall reactivated the landslide deposits as debris flows (Rosli et al, 2021a). In this work, landslides were mapped on optical satellite images, whose availability depends on satellite revisit time and local weather conditions.…”
Section: Chain Of Hazards and Other Sources Of Epistemic Uncertaintymentioning
confidence: 99%
“…This seismic event continued for approximately 30 s. It was detectable as far as 400 km from the epicentre, which, situated nearly 10 km deep, was the most significant earthquake in Malaysia since the Mw 6.2 Lahad Datu earthquake in 1976 (Adnan and Harith 2017;Tongkul 2016). According to Rosli et al (2021), the primary hazard of the earthquake involved direct geological failures, which was observed at the foot slope of Mount Kinabalu, the tallest mountain in the region and the centrepiece of Kinabalu Park (UNESCO World Heritage Site. Widespread rockfalls and numerous landslides were triggered by the mainshock and a series of aftershocks near Mount Kinabalu, forming a temporary landslide dam.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary hazard identified as debris flow occurred along the river channels. Rosli et al (2021) reported two debris flows, i.e. the Mesilau watershed of Kundasang on the Southeast flank of Mount Kinabalu and the Kadamaian watershed of Kota Belud, located on the northwest flank of Kota Belud.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have also developed models for debris flow similar to the SIMLAR, such as HyperKanako [18,19] Flo-2D [20], RAMMS [19,20] Flow-R [21], and DebrisFlow Predictor [22]. Takebayashi and Fujita developed a model for debris flow based on a two-dimensional continuum body model [23].…”
Section: Introductionmentioning
confidence: 99%